(untitled) (Bangladesh Agronomy Journal, 2021)
The field experiment was conducted at Agronomy research field, Joydebpur, Gazipur (Latitude: 23.999941, Longitude: 90.420273), RARS, Jamalpur (Latitude: 24.923025, Longitude: 89.950111) and ARS, Rajbari, Dinajpur (Latitude: 25.63544, Longitude: 88.65144) of BARI during rabi of 2018 – 2019 to observe the growth behavior and yield of wheat as influenced by prevailing air temperature based on sowing time. There were five sowing dates viz., D1 = 10 November, D2 =20 November, D3 = 30 November, D4=10 December and D5=20 December. Sowing date showed great influence on TDM production, LAI, physiological maturity, yield and yield components of wheat. 30 November sowing produced the maximum TDM and LAI followed by 20 November sowing. These parameters finally contributed to higher grain yield than earlier and later sowing date. The crop sown on 30 November took the longest period (105, 106 and 109 days, respectively) to attain the physiological maturity with the highest GDD (1639, 1638 and 1640 respectively) and 20 December sown crop took the shortest period (95 , 96 and 98 days respectively) to attain the physiological maturity with the lowest GDD (1530, 1528 and 1525 at Joydebpur, Jamalpur and Rajbari, respectively).It was also found that 30 November sown crop produced the higher grain yield (4.90 t ha-1, 4.99 t ha-1 and 5.03 t ha-1 at Joydebpur, Jamalpur and Rajbari, respectively).The results revealed that 20-30 November sowing produced higher grain yield might be due to favourable air temperature for growth and development. Late sowing after November 30 produced lower grain yield due to high temperature prevailed at the later growth stage (March) of wheat at Joydebpur, Jamalpur and Rajbari region. The temperature co-efficient of wheat was estimated at 2.41 t ha-1 (1.95-2.89 t ha-1) indicated grain yield reduced 2.41 t ha-1 per 1°C increased of air temperature and effect of temperature on the grain yield of wheat was estimated at 81-84%. Bangladesh Agron. J. 2020, 23(2): 69-80